Digital speed and position control system incorporating an Incremental encoder - Yaziz, Nor Hidayah (2014)
Nowaday Direct current (DC) motor become an important drive configuration for many applications across a wide range of powers and speeds. The ease of control and excellent performance of the DC motors will ensure that the number of applications using them will continue grow for the foreseeable future. This project focuson DC motor functional applications in term of speed control and position control system by using microcontroller PIC18F4520. Speed control system is a closed-loop real time control system, where optical encoder is coupled to the motor shaft to provide the feedback speed signal to controller. Pulse Width Modulation (PWM) technique is used where its signal is generated in microcontroller. The microcontroller will send PWM signal to motor driver, vary the voltage supply of motor to maintain at constant speed. While position control system are using Propotional Intergral Derivative (PID) controller as control method to get desired position with minimun error. The value of PID are define by using manualy method. Microcontroller acts as proportional, intergral and derivative (PID) controller with Kp =0.6, Ki=0.9 and Kd=0.1 in this study. Meanwhile Visual Basic 6.0 software is developed to provide a graphic user interface (GUI) for the user interfacing at computer. In addtional, it also shows a graph of motor position versus time to let the user monitor the performance of the system easily. Based on the result, the reading of optical encoder built is quite reliable. Through the project, it can be concluded that microcontroller PIC 18F4520 can control motor speed and motor position at desired value.